2016
DOI: 10.1111/ppa.12571
|View full text |Cite
|
Sign up to set email alerts
|

HRM analysis provides insights on the reproduction mode and the population structure of Gnomoniopsis castaneae in Europe

Abstract: Gnomoniopsis castaneae is an emergent nut rot agent of chestnut in southern Europe. To elucidate its population genetics, three simple sequence repeat (SSR) and two hypervariable markers were developed and assessed through high‐resolution melting (HRM) analysis on 132 isolates collected from 10 sites in Italy, France and Switzerland. High allele diversity (ranging from 0.23 to 0.40 depending on site) and number of haplotypes (49) were observed. More than 70% of the molecular variance could be accounted among i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…For instance, population studies demonstrated that bay leaves harbor a few dominant genotypes, which are persistent through time (Mascheretti et al 2009), precisely as expected when the host is epidemiologically relevant (Eyre et al 2013). In most infectious diseases, including SOD, infectious outbreaks are caused by highly transmissive genotypes or strains that are overly represented when compared to other genotypes (Berbegal et al 2013, Gramaje et al 2014, Sillo et al 2017). On the contrary, in substrates with nil or negligible epidemiological role, either a high turnover of genotypes occurs (e.g., in water and soil), or genetic structural variations causing a significant change in phenotype can be observed (e.g., in oaks; Eyre et al 2013Eyre et al , 2014.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, population studies demonstrated that bay leaves harbor a few dominant genotypes, which are persistent through time (Mascheretti et al 2009), precisely as expected when the host is epidemiologically relevant (Eyre et al 2013). In most infectious diseases, including SOD, infectious outbreaks are caused by highly transmissive genotypes or strains that are overly represented when compared to other genotypes (Berbegal et al 2013, Gramaje et al 2014, Sillo et al 2017). On the contrary, in substrates with nil or negligible epidemiological role, either a high turnover of genotypes occurs (e.g., in water and soil), or genetic structural variations causing a significant change in phenotype can be observed (e.g., in oaks; Eyre et al 2013Eyre et al , 2014.…”
Section: Discussionmentioning
confidence: 90%
“…, Sillo et al. ). On the contrary, in substrates with nil or negligible epidemiological role, either a high turnover of genotypes occurs (e.g., in water and soil), or genetic structural variations causing a significant change in phenotype can be observed (e.g., in oaks; Eyre et al.…”
Section: Discussionmentioning
confidence: 99%
“…SSR-based markers are widely used and popular due to their high reproducibility and multiallelic nature, and their power for genetic characterization of populations of wood decay fungi has been demonstrated (Franzen, Vasaitis, Penttilä, & Stenlid, 2007;Gonthier et al, 2015;Maurice, Skrede, LeFloch, Barbier, & Kauserud, 2014;Travadon et al, 2012). The analysis of SSRs coupled with HRM is a robust and reproducible method (Ganopoulos, Argiriou, & Tsaftaris, 2011), as it has been successfully used in genotyping of plants (Distefano, Caruso, La Malfa, Gentile, & Wu, 2012;Xanthopoulou et al, 2014), and, more recently, of fungal pathogens (Sillo et al, 2017;Zambounis, Xanthopoulou, Karaoglanidis, Tsaftaris, & Madesis, 2016). The HRM genotyping of the ten SSR markers allowed to distinguish all isolates from one another.…”
Section: Discussionmentioning
confidence: 99%
“…The interest of forest pathologists in unraveling environmental factors driving plant diseases has been amplified in the last decades by the onset of relevant epidemics caused by emerging pathogens such as Phytophthora ramorum Werres, De Cock and Man in't Veld in Western North America, Heterobasidion irregulare Garbelotto and Otrosina, Hymenoscyphus fraxineus (T. Kowalski) Baral, Queloz and Hosoya, and Gnomoniopsis castaneae G. Tamietti in Europe, just to cite a few relevant examples [3][4][5][6][7][8][9][10][11][12]. The main environmental drivers underlying the success of such novel epidemics have often been identified through a numerical ecology approach, based on computational and multivariate statistical techniques suitable to deal with complex ecological datasets [10,11,[13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%